Síntese, caracterização e estudo da química de coordenação de novos compostos contendo Índio e Telúrio - Mello, Melina de Azevedo (2011)
In this work we describe the synthesis and characterization of the first indium and tellurium compounds in which tellurium shows metallic behavior towards indium. We have studied the coordination chemistry of indium and tellurium, in different oxidation states and in the presence of different ligands, in order to understand the interactions that occur between these species. Indium(III) halides - InX3 (X = Cl, Br) react with phenyltellurium(IV) trihalides - PhTeX3 (X = Cl, Br) and hard ligands such as OPPh3, 1,10-phenantroline and DMSO, to yield [InX2(OPPh3)4]+[PhTeX4]- (X = Br, 1; X = Cl, 2), [InBr2(1,10-phen)2]+[PhTeBr4]- (3) and [InBr2(DMSO)4]+[PhTeBr4]- (4). Differently, with soft ligands such as thioureas, the reduction reaction of Te(IV) to Te(II) is favored. When PhTeX3 is substituted by TeCl4 the Lewis acid character of In(III) prevails over the hard/soft relation between In and Te. This leads to the formation of a compound containing only In, [InCl2(OPPh3)4]+[InCl4]- (5). No reaction is observed between InX3 and Te(II) species with hard or soft ligands. The compound [InI2(DPPMO2)2]+[InI4]- (6) (DPPMO2 = bis(diphenylphosphine)methane dioxide), obtained from the reaction between InI3 and PhTeI phenyltellurium(II) iodide indicates that reaction between In(III) and Te(II) does not occur due to once more prevails the Lewis acid character of In(III) over the hard/soft relation between In and Te.